Co-creation within hybrid networks: what can be learnt from the difficulties encountered? The example of the fight against blood- and sexually-transmitted infections. (September 2018) - Touati, Nassera; Maillet, Lara
This article analyses co-creation processes within hybrid networks. Specifically, it looks at a particular co-creation mechanism, in this case, a strategic community set up to test new ways of dealing with blood- and sexually-transmitted infections in Quebec. A strategic community is a temporary structure of inter-organizational collaboration, made up of professionals, first-level managers, general practitioners, representatives of community organizations, etc. tasked with generating, implementing and evaluating new ideas about the organization of services. The results of this study highlight the difficulties encountered as well as the issues related to these co-creation processes. Notes for practitioners: The implementation of co-creation processes, involving public, private and community actors, has to contend with numerous challenges: (1) the enrolment of the stakeholders concerned by the complex issues; (2) the creation of places for discussion and experimentation involving actors who play an important role in the implementation of change; (3) the mobilization of tools and facilitators to develop a common vision; (4) the action stage to validate new ways of doing things.